2014
DOI: 10.1002/hbm.22611
|View full text |Cite
|
Sign up to set email alerts
|

Nonphysiological factors in navigated TMS studies; Confounding covariates and valid intracortical estimates

Abstract: It is necessary to partition physical and physiological variance in TMS studies to make confounded data interpretable. The spatial resolution of nTMS is <5 mm and the EF-estimates are valid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 75 publications
(137 reference statements)
2
48
0
Order By: Relevance
“…During a TMS session where the user placed the coil over the scalp using a virtual interface that displayed the system’s output (x, y, z, roll, pitch, and yaw) as feedback, we were able to locate the coil over the target area with high accuracy, which was verified using a commercial 3D camera system. The amount of error seen while using our system was similar to that seen in the literature for other frameless stereotaxic systems, which are estimated to be up to 5mm (Forster et al, 2014; Julkunen et al, 2009; Schmidt et al, 2015; Sparing et al, 2008). Additionally, we found that when using our low-cost system during TMS on human subjects, the measured MEPs were larger than those collected by placing the coil without any feedback (non-navigated).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…During a TMS session where the user placed the coil over the scalp using a virtual interface that displayed the system’s output (x, y, z, roll, pitch, and yaw) as feedback, we were able to locate the coil over the target area with high accuracy, which was verified using a commercial 3D camera system. The amount of error seen while using our system was similar to that seen in the literature for other frameless stereotaxic systems, which are estimated to be up to 5mm (Forster et al, 2014; Julkunen et al, 2009; Schmidt et al, 2015; Sparing et al, 2008). Additionally, we found that when using our low-cost system during TMS on human subjects, the measured MEPs were larger than those collected by placing the coil without any feedback (non-navigated).…”
Section: Discussionsupporting
confidence: 81%
“…It has been recognized as an effective tool for quantifying corticospinal excitability in cognitive and clinical neuroscience using single or dual pulse techniques (Bestmann and Krakauer, 2015; Chen et al, 2008; Edwards et al, 2013), and for neurorehabilitation of many neuromuscular and psychiatric disorders by means of repetitive TMS (Hallett, 2007; Hoogendam et al, 2010; Levkovitz et al, 2015; Saba et al, 2015; Sun et al, 2012; Wang et al, 2014). However, outcomes of TMS experiments can be confounded by the accuracy of coil positioning over the target area (Bestmann and Krakauer, 2015; Burke et al, 1995; Kiers et al, 1993; Schmidt et al, 2009), as slight changes in stimulator coil location/orientation could alter current flow across neurons (Di Lazzaro et al, 2001; Schmidt et al, 2015; Werhahn et al, 1994). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, increasingly more attention is being paid to assessing the variability and repeatability in TMS studies (Beaulieu et al 2017;Goldsworthy et al 2016;Guerra et al 2017;Schmidt et al 2015), which is needed to establish the reliability of these excitability measures. The large inter-individual variation seems to be a common aspect in both TMS-EMG and TMS-EEG that hampers not only the clinical use in epilepsy, but also its potential application in other diseases and neuroscience research in general.…”
Section: Future Perspectivesmentioning
confidence: 99%